Respuesta :

leele1

Hiya. I'm going to rewrite the second equation.

By subtracting 5x by both sides, I'll be able to have y by itself:

-y=-5x+13

I'm going to then divide both sides by -1 to get:

y=5x-13.


Then, I'm going to plug that equation into the first equation

3x+2(5x-13)=39

Factor:

3x+10x-26=39

Combine like terms:

13x=65

Divide both sides by 13 to get x by itself to get x=5


Plug this back into the equation of y=5x-13

y=5(5)-13 to get y=12

Solve: 3x + 2y = 39; 5x - y = 13


I will try to solve your system of equations:

5x - y = 13; 3x + 2y = 39


Solve 5x - y = 13 for y:


5x - y + - 5x = 13 + - 5x (add - 5x to both sides):


- y = - 5x + 13


- y/ - 1 = - 5x + 13/ - 1 (Divide both sides by - 1):



y = 5x - 13



Substitute 5x - 13 for y in 3x + 2y = 39


3x + 2y = 39


3x + 2(5x - 13) = 39


13x - 26 = 39 (Simplify both sides of the equation)


13x - 26 + 26 = 39 + 26 (Add 26 to both sides):


13x = 65


13x/13 = 65/13 (Divide both sides by 13)


x = 5




Substitute 5 for X in Y = 5x - 13


y = 5x - 13


y = (5)(5) - 13


y = 12 (Simplify both sides of the equation):



Answer: y = 12 and x = 5






Hope that helps!!!!! (Answer: y = 12 and x = 5).